EFEKTIVITAS PROGRAM BIMBINGAN BELAJAR MATEMATIKA DALAM MEMPERKUAT PEMAHAMAN KONSEP DASAR OPERASI HITUNG SISWA SEKOLAH DASAR - Yulinda Sari, Desi; Izzah, Laelatul; Ahyan, Shahibul; Wardi, Zaowatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics is a fundamental subject that plays an essential role in developing students' logical, critical, and analytical thinking skills. However, many elementary school students still experience difficulties in understanding the basic concepts of arithmetic operations, which affects their overall mathematics achievement. This study aimed to analyze the effectiveness of a mathematics tutoring program based on the Contextual Teaching and Learning (CTL) approach in strengthening elementary students' understanding of basic arithmetic operations. The study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The participants consisted of 30 elementary school students who joined a mathematics tutoring program during the Community Service Program (Kuliah Kerja Nyata/KKN) in Dusun Kebon Dewa, Desa Kalianyar, from June to July 2026. Data were collected through pretest and posttest instruments and analyzed using descriptive statistics and the Normalized Gain (N-Gain) method. The findings revealed that the students' mean score increased from 55.17 on the pretest to 81.50 on the posttest, with an N-Gain value of 0.58, indicating a moderate level of improvement. These results demonstrate that the CTL-based mathematics tutoring program effectively improved students' understanding of addition, subtraction, multiplication, and division concepts by connecting mathematical learning with real-life situations and actively engaging students in meaningful learning experiences. Therefore, the program can serve as an effective non-formal learning strategy to strengthen elementary students' numeracy skills and conceptual understanding of mathematics.